2015
DOI: 10.1177/0748233714566875
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic cadmium exposure on the tissue distribution of copper and zinc and oxidative stress parameters in rats

Abstract: The aim of this study was to investigate the effect of oral cadmium (Cd) intoxication on the antioxidant response and its relationship with essential bioelements like copper (Cu) and zinc (Zn). The experimental group was chronically exposed to Cd daily for 8 weeks via consumption of water containing 15 ppm cadmium chloride. Cu, Zn, and Cd concentrations and oxidative stress parameters were analyzed in liver, kidney, and heart tissues. Exposure to Cd led to a significant decrease in the activities of superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
3
13
0
2
Order By: Relevance
“…The results of the present studies show that after subchronic administration of a modest dose (0.6 mg/kg SC, 5 days per week for 6–12 weeks), Cd causes significant changes in the renal cortical levels of several key metals, particularly Cu, Se, Fe and Zn. It should be noted that even though many previous studies have shown that Cd can alter renal levels of these metals [11] , [26] , [55] , [53] , there are several aspects of the present studies that are unique and merit special attention.…”
Section: Discussionmentioning
confidence: 94%
“…The results of the present studies show that after subchronic administration of a modest dose (0.6 mg/kg SC, 5 days per week for 6–12 weeks), Cd causes significant changes in the renal cortical levels of several key metals, particularly Cu, Se, Fe and Zn. It should be noted that even though many previous studies have shown that Cd can alter renal levels of these metals [11] , [26] , [55] , [53] , there are several aspects of the present studies that are unique and merit special attention.…”
Section: Discussionmentioning
confidence: 94%
“…Decreased SOD activity in fish exposed to Cd may be related to the reduced availability of bioelements such as Zn or Cu, which are components of SOD, as a result of their binding to metallothionein. Moreover, SOD activity may also be inhibited by the displacement of Mn ions from the active site of MnSOD and Cu and/or Zn ions from CuZnSOD by cadmium (Jurczuk et al 2004 ; Mukherjee et al 2010 ; Erdem et al 2016 ). It is very probable as an increased accumulation of Zn and Cu was noted in our study of the hepatopancreas in fish exposed to the highest concentration of cadmium (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Erdem O et al reported that superoxide dismutase activity in liver, heart, and kidney decreased and glutathione peroxidase activity significantly increased accompanied by reduced Cu and Zn after SD rats were given 15mg/L of cadmium chloride orally for 8 weeks. Their results suggest that a high concentration of Cd might affect the concentration of biological elements, such as Cu and Zn, in vivo [38,39]. In addition, a suitable concentration of Zn had an antagonistic effect on the toxicity of Cd.…”
Section: Discussionmentioning
confidence: 99%